COVID-19 and Gender Role in Unemployment: How Women in Special Capital Region of Jakarta is Less Likely to be Unemployed During Economic Disturbance - Rahman, J.H. (EDP Sciences, 2021)
The gender gap that occurs in Special Capital Region of Jakarta, between men and women has an impact on aspects of employment related to labor absorption. Increasing the number of optimal employment opportunities, both in terms of productivity and efficiency, can determine the success of economic development in a region. This study was conducted to see how likely it is that women are unemployed, in relation to the employment aspect in Special Capital Region of Jakarta which is based on secondary data from BPS and analyzed with a descriptive quantitative approach. The results showed that the open unemployment rate (TPT) in Special Capital Region of Jakarta in 2019-2020 experienced a significant increase in 2020, namely 4.86 for men and 4.5 for women. Different results are shown in the variable labor force participation rate (TPAK), which tends to experience a fluctuating trend with the participation rate of men being higher than women. In general, the COVID-19 pandemic has an impact on employment, which in turn has an impact on unemployment. During the COVID-19 pandemic, the unemployment rate was dominated by men, due to the high wages of men compared to women. In addition, women's labor force participation rates are relatively low compared to men's, causing women to have little chance of being unemployed. Female workers have higher resilience than male workers, this is due to the higher saturation of women in informal economic activities with entrepreneurship. Entrepreneurial activities tend to have more resilience than formal workers because there is no risk of termination of employment from the employer. Â© The Authors, published by EDP Sciences.